Pengaruh Kualitas Sumber Daya Manusia dan Komitmen Kerja Terhadap Kinerja Pegawai Kantor Kependudukan dan Pencatatan Sipil Kota Bima - Iwan Kurniawan; Mulyadin Mulyadin (Journal of Business and Economics Research (JBE), 2020)
This study aims to determine the effect of human resource quality and work commitment on employee performance. The research method used in this study is associative research, the research instrument used is a questionnaire / questionnaire. The population in this study were 69 employees of the Bima City Population and Civil Registry office (DUKCAPIL) with a sample of 58 Bima City Population and Civil Registry office employees, with the sampling technique using the slovin formula. sampling technique used (simple random sampling). The analytical tool used is SPSS version 22 for windows. The results of this study showed that the quality of human resources and work commitments did not have a positive and significant effect on the performance of the Bima City Civil Population and Registration Office employees, but simultaneously the quality of human resources and work commitments did not have a positive and significant effect on the performance of the Population and Registration Office employees. Civil City of Bima